Predictors of Futile Recanalization in Patients With Basilar Artery Occlusion With Large Versus Nonlarge Infarcts - Pan Zhang; Miaomiao Hu; Yingjie Xu; Jinghui Zhong; Xinfeng Liu; Wen Sun (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Basilar artery occlusion is associated with high rates of disability and mortality, and despite advances in endovascular treatment, futile recanalization remains a challenge. This study aims to identify predictors of futile recanalization in patients with basilar artery occlusion, focusing on large and nonlarge infarcts. Methods and Results This multicenter retrospective study included patients from 65 centers across China. Patients were categorized based on posterior circulation Alberta Stroke Program Early CT [Computed Tomography] Score (pc‐ASPECTS) into 2 groups: large infarcts (pc‐ASPECTS ≤6) and nonlarge infarcts (pc‐ASPECTS >6). Predictors of futile recanalization—defined as a modified Rankin Scale score of 4 to 6 at 90 days despite successful recanalization—were analyzed using logistic regression models. Among the 2075 patients, 1113 (53.6%) experienced futile recanalization. In patients with pc‐ASPECTS >6, predictors of futile recanalization included older age (odds ratio [OR], 1.18 [95% CI, 1.06–1.31]), higher National Institute of Health Stroke Scale scores (OR, 1.75 [95% CI, 1.58–1.94]), and prolonged time from puncture to reperfusion (OR, 1.24 [95% CI, [1.12–1.38]). Intravenous thrombolysis (OR, 0.85 [95% CI, [0.77–0.94]) and achieving modified Thrombolysis in Cerebral Infarction grade 3 (OR, 0.81 [95% CI, [0.74–0.90]) were associated with a lower likelihood of futile recanalization. In patients with pc‐ASPECTS ≤6, being male (OR, 0.75 [95% CI, 0.58–0.96]) and having higher pc‐ASPECTS scores (OR, 0.65 [95% CI, 0.48–0.85]) were protective against futile recanalization, whereas higher National Institute of Health Stroke Scale scores increased the risk (OR, 1.81 [95% CI, 1.42–2.32]). Conclusions This study identifies distinct predictors of futile recanalization in patients with basilar artery occlusion based on infarct size. The findings underscore the importance of individualized treatment strategies and timely intervention to optimize endovascular treatment outcomes in high‐risk patients.